2015
DOI: 10.1097/bpo.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Functional Loss With Displacement of Medial Epicondyle Humerus Fractures

Abstract: Our work provides a biomechanical explanation for anterior displacement of medial epicondyle fractures observed radiographically and motivates alternative methods of fracture assessment. A functional basis for determining acceptable displacement of medial epicondyle fractures is suggested; however, all individual clinical factors should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The obtained questionnaire history included age at time of injury, current age, hand dominance, treatment method, length of immobilization, need for formal physical therapy, pre- and postinjury athletic level (specifically inquiring about participation in overhead sports), subsequent treatment including further surgeries, current symptoms, and treatment satisfaction. Prospective objective data collection included radiographs (standard anteroposterior and lateral radiographs, as well as the axial distal humerus view) [ 11 ], physical examination, and grip strength testing with a Jamar dynamometer. Physical examination motion and alignment measurements were all recorded using a goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained questionnaire history included age at time of injury, current age, hand dominance, treatment method, length of immobilization, need for formal physical therapy, pre- and postinjury athletic level (specifically inquiring about participation in overhead sports), subsequent treatment including further surgeries, current symptoms, and treatment satisfaction. Prospective objective data collection included radiographs (standard anteroposterior and lateral radiographs, as well as the axial distal humerus view) [ 11 ], physical examination, and grip strength testing with a Jamar dynamometer. Physical examination motion and alignment measurements were all recorded using a goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…Irrespective of a relatively low rate of bony union, the nonsurgical treatment provides good to excellent functional results. [ 19 22 ] However, the nonsurgical treatment with cast application and immobilization of fractured elbow is increasingly being replaced by surgical fixation. [ 16 , 19 ] The primary purpose of surgical fixation is to achieve an anatomic reduction and early mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 22 ] However, the nonsurgical treatment with cast application and immobilization of fractured elbow is increasingly being replaced by surgical fixation. [ 16 , 19 ] The primary purpose of surgical fixation is to achieve an anatomic reduction and early mobilization. Kamath et al found a significantly higher union rate in operative fixation (92.5%) than nonoperative management (49.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional treatment algorism for moderate displaced ones suggests cast immobilization when the displacement is less than 5mm, and operation when the displacement is more than 5mm [1,5]. A research by Edmonds [16] et al did show the relationship between displacement amount and outcomes like wrist flexion strength (approximate 2% decrease for every 1mm of anterior displacement due to muscle shortening). Yet the deemed displacement was usually measured on AP or lateral plain X-rays, which was with great deviation and did not represent the true displacement of the fracture, making it hard to justify the treatment strategy [17].…”
Section: Discussionmentioning
confidence: 99%